2014
DOI: 10.1103/physrevc.89.011001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive dependence of isotope and isobar distributions of limiting temperatures on the symmetry energy

Abstract: The mass, isotope, and isobar distributions of limiting temperatures for finite nuclei are investigated by using a thermodynamics approach together with the Skyrme energy density functional.The relationship between the width of the isotope (isobar) distribution of limiting temperatures and the stiffness of the density dependence of the symmetry energy clearly is observed. The nuclear symmetry energy with smaller slope parameter L sym causes a wider the isotope (isobar) distribution of limiting temperatures. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…While the asymmetry energy of nuclear matter is relatively well understood in the ground-state [6], heavyion collisions provide the ability to probe the EoS away from ground-state density and temperature. Numerous experiments have been conducted in order to place constraints on the density dependence of the asymmetry energy through a variety of experimental observables such as free neutron-proton ratios [6,8,9], isobaric yield ratios [10][11][12][13], isoscaling [12,[14][15][16][17][18][19][20][21][22][23][24][25], isospin diffusion [2,21,[26][27][28][29][30], collective flow [31][32][33][34][35][36][37] and neck dynamics/emission [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the asymmetry energy of nuclear matter is relatively well understood in the ground-state [6], heavyion collisions provide the ability to probe the EoS away from ground-state density and temperature. Numerous experiments have been conducted in order to place constraints on the density dependence of the asymmetry energy through a variety of experimental observables such as free neutron-proton ratios [6,8,9], isobaric yield ratios [10][11][12][13], isoscaling [12,[14][15][16][17][18][19][20][21][22][23][24][25], isospin diffusion [2,21,[26][27][28][29][30], collective flow [31][32][33][34][35][36][37] and neck dynamics/emission [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, observables that were linearly-dependent [10,29] on the isospin composition of a source were used as surrogates for the actual ∆ QP . Several observables have been suggested that fit this criterion including free n/p ratios [6,9], isobaric yield ratios [11,13,29], charged pion ratios [9] and the isoscaling parameter α [10,17,18,21]. The degree of equilibration can be quantified by determining isospin asymmetry of the hot source after the reaction, and comparing it to the initial state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Li Ou et al studied isobar distributions of T lim for tin nuclei. They use Skyrme forces with different asy-stiffnesses [24], in the framework of a nucleus in equilibrium with its vapor [15]. Results are shown in fig.…”
Section: The Caloric Curvementioning
confidence: 99%
“…• experimentally determined caloric curves all present a similar shape whatever the mass of the system (A=30-240), namely a Fermi gas Adapted from [15].…”
Section: Phase Transition In Finite Systemsmentioning
confidence: 99%